Gendering the Portuguese-Speaking World
1 online resource.
Keywords: "In this book, 14 scholars from Belgium, Canada, Mozambique, Portugal, the US, and the UK examine the long-term cultural and social environment of sex definition in different continents. The study of medieval and early modern Portugal shows limited rights of women and patriarchal constraints. The impact on gender definition of Portuguese expansion in Africa, Asia, and the New World is analysed with the inclusion of local agency informing indigenous responses. Unstable constructions of masculinity, femininity, queer, homosexual, bisexual, and transgender identities and behaviours are placed in historical context. The use of language and literary representation are part of this research. Contributors are: Darlene Abreu-Ferreira, Vanda Anastácio, Francisco Bethencourt, Dorothée Boulanger, Rosa Maria dos Santos Capelão, Maria Judite Mário Chipenembe, Gily Coene, Philip J. Havik, Ben James, Anna M. Klobucka, Chia Longman, Amélia Polónia, Ana Maria S. Rodrigues, Isabel dos Guimarães Sá, Ana Cristina Santos, and João Silvestre"--